Fajki oraz sposoby używania tytoniu na obszarze obecnych zachodnich ziem polskich od XVII do początku XX wieku - Gil, Łukasz (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2011)
Clay pipes are common category of archaeological data. These are very interesting and useful artifacts. In most cases, their chronological position and the place of origin are easy to determine. The first clay pipes appeared in the western areas of present-day Poland in the beginning of the 17th century. They were made by pipe makers from Amsterdam and Gouda City (Holland). In the second half of the 17th century in southern part of western areas of present-day Poland or in their neighbourhood, local manufactures producing clay pipes for local market – Śląsk, eastern Saksonia and southern Branderburgia, were established. The products from Gouda were the most popular in the first half of the 18th century. Machiel Brem, Hendrick Manshoofd, Lucas de Jong, Jacob de Vos, Danens’ Family manufacture and Frans Verzijl were among their biggest exporters to western areas of present-day Poland. From the second half of the 18th century, the pipe makers from Gouda had to compete with products of local manufactures, such as Rościn, Zborowskie and Weissenspring. Stub-stemmed pipes came to western areas of present-day Poland from Turkey around the middle of the 17th century. It is worth mentioning that drawing snuff was very popular in the western areas of present-day Poland in the 18th century, but cigars and cigarettes became more popular only in the following centuries.
Pipes and tobacco use in western areas of present-day Poland in the period between the 17th and the beginning of 20th century